PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Kasus Karyawan PT.Telekomunikasi,Tbk Batam) - Denni Fitri Iswantri; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study dilaksnakan on PT.Telekomunikasi , Tbk Batam in Jl . Attorney General R. Suprapto , SH Sekupang Batam . The problem formulation is How does Organizational Commitment on Employee Performance in PT.Telekomunikasi, Tbk Batam. The population in this study were all permanent employees PT.Telekomunikasi , Tbk Batam . Sampling was done by making the overall population of respondents ie 66 people . Source data from the primary data and secondary data . Data collection techniques in this study is through questionnaires and interviews . While sampling techniques accidental sampling . The analytical method used is descriptive quantitative method using a simple linear regression with SPSS.The results of this study indicate that organizational commitment variable positive and significant effect on the performance of employees on PT.Telekomunikasi , Tbk Batam . Organizational commitment and a positive and significant effect is more dominant variables affect the performance of employees PT.Telekomunikasi , Tbk Batam . Simultaneous test showed that organizational commitment variables have a significant effect on the performance of employees at PT.Telekomunikasi , Tbk, Batam , which is described by the coefficient of determination ( r² ) . Organizational commitment variables can explain the variable performance of employees by 29.7 % while the remaining 70.3 % is explained by other variables not examined in this study .Keywords : Organizational Commitment,Employee Performance